Employability in online higher education : a case study - Silva, Ana Paula (2015)
This paper presents the results of a study on the perceptions of students and teachers from a distance education university on employability skills in higher education. The choice of skills that are important to the labour market has been the subject of controversy because it involves heterogeneous interests of different groups. Our case study departs from the following question: what are the perceptions of students and teachers about online higher education and the required skills for employability? To this end, a comparative study on the views of students and teachers was conducted, which emphasized the following dimensions: a) the most important skills for employability, and b) the skills to be developed for employability within undergraduate degrees in online learning. To collect the required data, a questionnaire was prepared and applied to students and teachers, taking as its main reference the theoretical model of Knight and Yorke (2006). In spite of the specificity of each group, the results reveal some similarities between students and teachers with regard to employability. The conclusions also highlight the need to promote research in this area in the European context.